The Effects of Urea, Vermicompost and Azocompost on Some Traits of Sweet corn Cultivars under Water Deficit Stress - Maryam Rahimi Gavdanehgodari; Mohammad Ali Mohammad Modarres-SanavyModares; Majid Aghaalikhani; Ali Heidarzadeh (Journal of Agricultural Science and Sustainable Production, 2020)
In order to investigate some characteristics of three sweet maize varieties under application of various fertilizers and water deficit stress at the reproductive stage, a field experiment was conducted in Tarbiat Modares University during the 2016 growing season. The experiment was performed at three replications with the Factorial Split Plate arrangement in a completely randomized block design. Factors of irrigation regimes as irrigation after discharging 25, 40 and 55% of water used and cultivars (Basin, Passion and KSC403) in the main plot and fertilization included urea (116 kg.ha-1), azocompost (15497 kg.ha-1) and vermicompost (24223 kg.ha-1) in the subplot were studied. The results showed that the highest ear fresh weight (236.77 g.m-2) was observed in optimum irrigation conditions. Grain yield was significantly affected only by fertilization (p≤0.05). The application of urea fertilizer increased grain yield, while the use of azocompost decreased it. The highest and lowest ear fresh weight were obtained in Passion and KSC403 cultivars, respectively. Passion cultivar in severe water stress and Basin cultivar in moderate water stress and optimum irrigation was produced the highest ear fresh weight and KSCO403 cultivar showed the lowest amount in all irrigation regimes. The highest amounts of chlorophyll a and b were obtained with 1.74 and 0.47 mg.g-1 fresh weight, respectively, from optimal irrigation. Vermicompost (only 4% decrease compared to control) and urea, (about 13% more than control) respectively, under sever water stress and moderate water stress conditions, somewhat controlled the effect of water shortage in Passion cultivar and increased the ear fresh weight.